0
$\begingroup$

I am asked to show that the pseudosphere has Gaussian Curvature $-1$ at all points. So I parametrized the tractrix as: \begin{equation} \alpha(t) = (\sin{t},\cos{t}+\log{\tan{\frac{t}{2}}}) \end{equation} So the surface of revolution would be: \begin{equation} x(\theta,t)=(\sin{t}\cos{\theta},\sin{t}\sin{\theta},\cos{t}+\log{\tan{\frac{t}{2}}}) \end{equation} By calculating the first and second fundamental forms we have that $F=f=0$ and $E=(\sin{t})^2,G=(\cot{t})^2,e=(\cos{t})^2$ and $g=-(\cot{t})^2$. So the Gaussian curvature is: \begin{equation} K = \frac{eg}{EG} = -(\cot{t})^2 \end{equation} What am I doing wrong?

$\endgroup$
  • 1
    $\begingroup$ Since you haven't shown the details of your computations, I can't tell you what you're doing wrong. But your $e$ and $g$ are most definitely wrong. Did you remember to take the unit normal vector? $\endgroup$ – Ted Shifrin Oct 16 '18 at 18:29
1
$\begingroup$

We have \begin{align} x_\theta &= (-\sin t\sin\theta, \sin t \cos \theta, 0) = \sin t(-\sin\theta, \cos\theta, 0) \\ x_t &= (\cos t \cos\theta, \cos t \cos\theta, -\sin t + \frac{\sec^2(t/2)}{2\tan(t/2)}) = \cos t(\cos\theta, \sin\theta, \cot t), \end{align} so \begin{align} E&= \langle x_\theta, x_\theta \rangle = \sin^2 t\\ F&= 0 \quad\text{[surface of revolution]}\\ G&= \langle x_t, x_t \rangle = \cos^2 t (1+\cot^2t) = \cot^2t. \end{align} So far so good. Now $x_\theta \times x_t$ is parallel to $$ (-\sin\theta, \cos\theta, 0) \times(\cos\theta,\sin\theta,\cot t) = (\cos\theta\cot t, \sin\theta\cot t, -1) $$ so we can (after normalizing to make it a unit vector, i.e. multiplying by $\sin t$) choose the Gauss map to be $$ N = (\cos\theta\cos t, \sin\theta\cos t, -\sin t). $$ This gives \begin{align} N_\theta &= (-\sin\theta\cos t, \cos\theta\cos t, 0)\\ N_t &= (-\cos\theta\sin t, -\sin\theta\sin t, -\cos t), \end{align} so that \begin{align} e &= - \langle N_\theta, x_\theta \rangle = -\sin t \cos t\\ f &= 0 \quad\text{[surface of revolution]}\\ g &= - \langle N_t, x_t \rangle = -\cos t (-\sin t - \cos t \cot t) = \cot t, \end{align} which gives $$ K = \frac{eg-f^2}{EG-F^2} = \frac{-\cos^2t}{\sin^2t\cot^2t} = -1. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.